Nicos Valsamakis – Casa Lanaras e casa Paraschis ad Anavyssos, Grecia - Mugnai, Francesca (Firenze Architettura, 2026)
Le ville Lanaras e Paraschis di Nicos Valsamakis (1961-1963) sono lette come espressione di un’idea di abitare, intesa in senso heideggeriano come apertura e custodia del mondo. Improntata a un principio compositivo di ascendenza miesiana, l’architettura si riduce a un sistema di piani che stabilisce una continuità con il paesaggio del Golfo Saronico. Ne emerge una modernità radicata, in cui ogni astrazione è ricondotta al suolo, alla luce e alla specificità del contesto greco. The Lanaras and Paraschis houses by Nicos Valsamakis (1961–1963) are interpreted here as expressions of a particular conception of dwelling, understood in a Heideggerian sense as an act of openness to and custodianship of the world. Drawing on a compositional logic rooted in Miesian principles, the architecture is articulated through a system of planes that establishes a profound continuity with the landscape of the Saronic Gulf. The result is a modernity that is rooted to the place, in which formal abstraction is always linked to the ground, the light and the specific features of the Greek context.